Electroenzymatic Sensors: A Mediator‐Free Electroenzymatic Sensing Methodology to Mitigate Ionic and Electroactive Interferents' Effects for Reliable Wearable Metabolite and Nutrient Monitoring (Adv. Funct. Mater. 10/2020). (3rd March 2020) - Cheng, Xuanbing; Wang, Bo; Zhao, Yichao; Hojaiji, Hannaneh; Lin, Shuyu; Shih, Ryan; Lin, Haisong; Tamayosa, Stephanie; Ham, Brittany; Stout, Phoenix; Salahi, Kamyar; Wang, Zhaoqing; et al.
Abstract : In article number 1908507, Sam Emaminejad and co‐workers report the fundamental challenges of conventional Prussian Blue‐based wearable enzymatic sensors, which need to be resolved for their reliable operation in complex biofluids. Accordingly, they devise an alternative mediator‐free wearable electroenzymatic sensing methodology, where the experimental results indicate high degrees of sensitivity, selectivity, and stability of the developed sensors for wireless biofluid analysis.